Pharmacokinetics of cannabidiol-/cannabidiolic acid-rich hemp oil in juvenile cynomolgus macaques (Macaca fascicularis) - Johns, Tinika N.; Wakshlag, Joseph J.; Lyubimov, Alexander V.; Zakharov, Alexander; Burnside, Wesley M. (Frontiers in Veterinary Science, 2023)
Cannabinoids are increasingly popular in human and veterinary medicine and have been studied as an alternative treatment for a wide range of disorders. The goal of this study was to perform a pharmacokinetic analysis of oral cannabidiol (CBD)-/cannabidiolic acid (CBDA)-rich hemp oil (CBD/ArHO) in juvenile cynomolgus macaques (Macaca fascicularis). After a 2 mg/kg CBD/ArHO pilot study, 4 and 8 mg/kg direct-to-mouth CBD/ArHO were administered (n = 4 per dose) once daily for 14 days and blood was collected at 0-, 0.5-, 1-, 2-, 4-, 8-, 12-, and 24-h, and on Days 7 and 14, to quantify serum cannabinoid concentrations by high-performance liquid chromatography–tandem mass spectrometry. Serum biochemistries and complete blood counts were performed on Days 0, 1, and 14. The maximum mean serum concentration (Cmax) of CBDA was 28.6–36.2 times that of CBD at 4 and 8 mg/kg. At 8 mg/kg, the Cmax of CBD was 1.4 times higher (P = 0.0721), and CBDA was significantly 1.8 times higher (P = 0.0361), than at 4 mg/kg. The maximum mean serum concentration of ∆9-tetrahydrocannabinol (THC) was 4.80 ng/mL at 8 mg/kg. Changes in serum biochemistries and complete blood counts over time were not clinically significant. Given the low serum CBD concentrations, the doses and frequency used in this study may be insufficient for a therapeutic effect of CBD in particular; therefore, clinical studies are needed to determine the therapeutic dose of CBD and CBDA for macaques, which may differ based on the disorder targeted.